Legal Analysis of Abuse of Power Practices in The Indonesian Tin Mining Industry: A Case Study of Harvey Moeis - Lubis, Rania Faradita; Kusuma, Eduardus; Hosnah, Asmak Ul (Syiar Hukum, 2024)
The corruption case involving Harvey Moeis revealed the practice of abuse of power in the tin mining industry in Indonesia. Harvey, as a representative of PT Refined Bangka Tin (RBT), is suspected of having made contact with the President Director of PT Timah, Mochtar Riza Pahlevi Tabrani, to accommodate illegal mining activities in the PT Timah Mining Business Permit (IUP) area. The agreement involves the provision of tin processing equipment in the PT Timah IUP area for several smelters, with profit sharing disguised as Corporate Social Responsibility (CSR). The CSR funds were channeled through PT QSE with the help of another suspect, Helena Lim. Harvey was charged with Article 2 Paragraph (1) and Article 3 jo. Article 18 of the Republic of Indonesia Law concerning the Eradication of Corruption Crimes. Harvey's detention by the Attorney General's Office marks a legal step in efforts to eradicate corruption and restore the integrity of the mining industry in Indonesia.